Spatial Analysis and Visualization of Edu-Tourism Clusters in MAMMINASATA, South Sulawesi: A GIS Approach to Attraction Identification and Classification - Haedar Akib; Didin Didin; Ahmad Wahidiyat Haedar; Khairil Asnan Haedar; Rudi Salam; Muh. Darwis; Muh. Ibrahim Halim (International Journal of Environment, Engineering and Education, 2026)
Educational tourism is increasingly understood as a spatially embedded learning resource system, yet its metropolitan-scale planning remains underexamined. This study analyzes the spatial distribution and land suitability of edu-tourism attractions in the MAMMINASATA Metropolitan Area, South Sulawesi, Indonesia, comprising Makassar, Gowa, Maros, and Takalar. Using a GIS-based weighted overlay approach, 36 georeferenced attractions were inventoried and classified into cultural, natural, man-made, and special-interest tourism. Spatial suitability was assessed through four criteria relevant to metropolitan planning: road accessibility, slope, vegetation density (NDVI), and proximity to activity centers. All datasets were standardized to a common suitability scale and integrated into a composite land-suitability model, after which suitability values were extracted at each attraction location. The results show that the edu-tourism resource base is dominated by natural attractions (44.40%) and cultural attractions (27.8%), with the strongest concentration in Makassar, Gowa, and Maros. The weighted overlay indicates that 66.63% of the study area is very suitable and 29.84% is suitable for edu-tourism development, meaning that 96.47% of the metropolitan area possesses supportive territorial conditions. At the site level, 58.3% of attractions are located in very suitable areas, 36.10% in suitable areas, and only 5.60% in moderately suitable areas, while no site falls into the not suitable class. These findings demonstrate that MAMMINASATA has strong potential for integrated edu-tourism planning, particularly in the Makassar-Gowa corridor, while more selective accessibility and service improvements are needed in parts of Maros and Takalar.